2018
DOI: 10.3389/fonc.2018.00648
|View full text |Cite
|
Sign up to set email alerts
|

Use of Radiomics Combined With Machine Learning Method in the Recurrence Patterns After Intensity-Modulated Radiotherapy for Nasopharyngeal Carcinoma: A Preliminary Study

Abstract: Objective: To analyze the recurrence patterns and reasons in patients with nasopharyngeal carcinoma (NPC) treated with intensity-modulated radiotherapy (IMRT) and to investigate the feasibility of radiomics for analysis of radioresistance.Methods: We analyzed 306 NPC patients treated with IMRT from Jul-2009 to Aug-2016, 20 of whom developed with recurrence. For the NPCs with recurrence, CT, MR, or PET/CT images of recurrent disease were registered with the primary planning CT for dosimetry analysis. The recurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 24 publications
1
36
0
Order By: Relevance
“…[ 42 ] Zhang et al found textural features correlate not just to local failure but also to distant treatment failure. [ 37 ] Another study by Li et al showed that 8 radiomics features could differentiate in field recurrence from pre-treatment spectral attenuated inversion-recovery T2-weighted (SPAIR T2W) MRI. [ 34 ] Zhang et al produced a radiomics signature built with 11 features that outperformed conventional clinical variables in predicting local recurrence-free survival in patients with non-metastatic T4 NPC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 42 ] Zhang et al found textural features correlate not just to local failure but also to distant treatment failure. [ 37 ] Another study by Li et al showed that 8 radiomics features could differentiate in field recurrence from pre-treatment spectral attenuated inversion-recovery T2-weighted (SPAIR T2W) MRI. [ 34 ] Zhang et al produced a radiomics signature built with 11 features that outperformed conventional clinical variables in predicting local recurrence-free survival in patients with non-metastatic T4 NPC.…”
Section: Discussionmentioning
confidence: 99%
“…[30,31] Magnetic resonance imaging (MRI) is the imaging of choice in the diagnosis and local staging in NPC due to its superior soft tissue contrast and allows for accurate delineation of target volumes for purposes of radiotherapy. [32][33][34][35][36][37] Whilst some research has been carried out on the application of radiomics in nasopharyngeal cancer, an approach that utilizes MRI radiomics as a predictive signature for intra-tumoral radio-resistance has not yet been developed. Comprehensive image analysis using radiomics that can identify radio-resistant tumor sub-volumes from pre-treatment MRI scans could guide individualized radiation therapy by suggesting target volumes in which a higher dose of radiation is needed for better tumor control.…”
Section: Introductionmentioning
confidence: 99%
“…Radiomics models are built based on handcrafted features, while deep learning learns the features automatically. In order to have better prediction, many researchers have proposed hybrid prediction models [95][96][97][98]. Another research group used the PyRadiomics platform, and extracted the imaging features of primary tumors in all patients who did not exhibit DM before treatment.…”
Section: Prediction Models For Recurrence Metastasis and Survivalmentioning
confidence: 99%
“…Being able to predict not only the risk of recurrence but also whether it would be locoregional or a distant metastasis (DM) may enhance treatment decisions. As a result, Li et al (82) explored the predictive power of radiomics for the type of recurrence (in field, out of field, marginal). After selection of the influential subset of radiomic features, Kruskal Wallis test and ROC analysis were employed for each feature to assess its capability on in field recurrence prediction.…”
Section: Tumor Control Probability Assessmentmentioning
confidence: 99%